Analysis Of A Green Economy-Based Digital Marketing Model Using Porter’s Five Forces Model On Micro, Small, And Medium Enterprises (Msmes) In Border Areas - Usman, Usman; Siokalang, Maria Angela; Rahmadi, Riski; Manggu, Blasius (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to describe how micro, small, and medium enterprises (MSMEs) can use Porter’s Five Forces approach to utilize sustainable digital marketing and increase product competitiveness in an increasingly competitive market. This study employs a qualitative descriptive approach, obtaining data from literature reviews and interviews with five informants from four clusters: agriculture, the creative industry, services, and culinary. NVivo 15 was used for qualitative data processing, and qualitative data analysis was carried out through data reduction, presentation, and conclusion-drawing. The obtained data were then validated through a problem-based learning (PBL)-based focus group discussion (FGD) process with all informants. The results of this study present a community-based green economy digital model with three pillars: a green economy, improved digital marketing infrastructure, and educational programs and mentoring services for MSMEs within the scope of the green economy in border areas.